PENERAPAN MODEL PEMBELAJARAN PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 12 PANGKALAN JAMBI - Budhi Andi Putra; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Indonesian language learning in class V SDN 12 Pangkalan Jambi, especially in the reading comprehension skills of students is still less than optimal. From the results of preliminary observations Obtained the data is that the average value of students in reading comprehension of children's story only Reached 53.50 (7 students) are skilled at reading comprehension. The purpose of this research is to improve the reading comprehension skills of children's story Grade Students of SDN 12 bases Jambi Application of Learning Model Preview, Question, Read, Reflect, Recite, Review (PQ4R). The research problems are: Is the Application of Learning Model Preview, Question, Read, Reflect, Recite, Review (PQ4R) can Improve Reading Comprehension Skills Student Class V SDN 12 Pangkalan Jambi?. The results of the study skills of reading comprehension Obtained from the children's story I cycle I UH and UH II in the second cycle. In the first cycle percentage value pemhamana children's story reading skills of students is 70.5 (medium category) and Increased in the second cycle with an average of 83.75 (high category. The results of the data to the analysis activities of teachers and students during the learning takes place in class V SDN 12 namely Jambi base percentage of teachers in implementing the learning activities in the first cycle of the first meeting 66.67% with enough categories and at the second meeting with a percentage increase of of 75.00% in both categories, and on the second cycle of the first meeting 87.5% excellent category and Increased again in the second meeting is 95.83% with the category very well, and the activity of students in the first cycle of the first meeting with a 62.5% enough category and the second meeting is 70.83% with both categories. in the second cycle of 83.33% of the first meeting with a good category and the second meeting is 91.67% with the category very well. From the results it can be seen that the Application of Learning Model Preview, Question, Read, Reflect, Recite, Review (PQ4R) can Improve Reading Skills understanding of children's story Grade Students of SDN 12 PangkalanJambi.Keywords: Application of Learning Model Preview, Question, Read, Reflect , Recite , Review ( PQ4R ) , reading comprehension Students